Recalibrating MSME Marketing Strategy: A Data-Audited SWOT-STP Robustness Analysis of Sinar Jaya Snack - Arifan Jaya Hartono; Haris Sandhi Yudha; Indra Gumelar (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2026)
This study re-examines the marketing strategy of Sinar Jaya Snack, a local Indonesian snack MSME, by replacing an under-specified qualitative design with a transparent secondary case-data reanalysis and robustness assessment. The source manuscript reported Internal Factor Evaluation (IFAS), External Factor Evaluation (EFAS), SWOT, and Segmentation-Targeting-Positioning (STP) results, but arithmetic inconsistencies were identified in factor-weight totals and several reported subtotals. The reconstructed method therefore performs a data-integrity audit, normalizes the published weights while preserving their relative structure, recomputes weighted scores, derives strategic SWOT coordinates, maps source-supported customer descriptors into operational STP archetypes, and evaluates quadrant stability through 50,000 bounded Monte Carlo perturbations. After normalization, the IFAS score is 2.698 and the EFAS score is 3.118. The strategic coordinates are 1.106 for the internal balance and 1.141 for the external balance, placing the business in a growth-oriented position. This posture remained positive in 100% of the sensitivity simulations under the specified perturbation ranges. The strongest actionable factors are affordable pricing, reseller appeal, local product acceptance, customer service, and small-pack flexibility, while restricted geographic reach and weak promotional penetration remain structural constraints. Rather than prioritizing immediate branch expansion, the analysis supports an asset-light sequence centered on reseller-network development, digitally enabled local reach, event-oriented bundles, and loyalty or volume pricing. The study contributes a reproducible approach for converting subjective SWOT-STP inputs into an auditable and uncertainty-aware strategic diagnosis for resource-constrained MSMEs.